More recent insights into the breast cancer burden across BRICS-Plus: Health consequences in key nations with emerging economies using the global burden of disease study 2019 - Mubarik, Sumaira; Luo, Lisha; Iqbal, Mujahid; Nawsherwan,; Bai, Jianjun; Yu, Chuanhua (Frontiers in Oncology, 2023)
Background Brazil, Russia, India, China, South Africa, and 30 other Asian nations make up the BRICS-Plus, a group of developing countries that account for about half of the world’s population and contribute significantly to the global illness burden. This study aimed to analyzed the epidemiological burden of female breast cancer (BC) across the BRICS-Plus from 1990 to 2019 and studied the associations with age, period, birth cohort and countries’ sociodemographic index (SDI). Methods The BC mortality and incidence estimates came from the 2019 Global Burden of Disease Study. We estimated cohort and period effects in BC outcomes between 1990 and 2019 using age-period-cohort (APC) modeling. The maximum likelihood (ML) of the APC-model Poisson with log (Y) based on the natural-spline function was used to estimate the rate ratio (RR). We used annualized rate of change (AROC) to quantify change over the previous 30 years in BC across BRICS-Plus and compare it to the global. Results In 2019, there were about 1.98 million female BC cases (age-standardized rate of 45.86 [95% UI: 41.91, 49.76]) and 0.69 million deaths (age-standardized rate of 15.88 [95% UI: 14.66, 17.07]) around the globe. Among them, 45.4% of incident cases and 51.3% of deaths were attributed to the BRICS-Plus. China (41.1% cases and 26.5% deaths) and India (16.1% cases and 23.1% deaths) had the largest proportion of incident cases and deaths among the BRICS-Plus nations in 2019. Pakistan came in third with 5.6% cases and 8.8% deaths. Over the past three decades, from 1990 to 2019, the BRICS-Plus region’s greatest AROC was seen in Lesotho (2.61%; 95%UI: 1.99-2.99). The birth cohort impacts on BC vary significantly among the BRICS-Plus nations. Overall, the risk of case-fatality rate tended to decline in all BRICS-Plus nations, notably in South Asian Association for Regional Cooperation (SAARC) and China-ASEAN Free Trade Area (China-ASEAN FTA) countries, and the drop in risk in the most recent cohort was lowest in China and the Maldives. Additionally, there was a substantial negative link between SDI and case fatality rate (r1990= -0.91, p<0.001; r2019= -0.89, p<0.001) in the BRICS-Plus in both 1990 and 2019, with the Eurasian Economic Union (EEU) nations having the highest case fatality rate. Conclusions The BC burden varies remarkably between different BRICS-Plus regions. Although the BRICS’ efforts to regulate BC succeeded, the overall improvements lagged behind those in high-income Asia-Pacific nations. Every BRICS-Plus country should strengthen specific public health approaches and policies directed at different priority groups, according to BRIC-Plus and other high-burden nations.